Pengelolaan dan Penggunaan Dana Desa Tanjungsari, Kecamatan Pacitan, Kabupaten Pacitan dalam Perspektif Hukum - Aida Fatma; Lego Karjoko (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The country of Indonesia has around 82.3% of its territory in villages. Based on Law Number 56 of 2015, the number of villages in Indonesia is 74,754 villages. Government policies are needed that support village development and empower village communities so that villages can be developed and village communities can develop. In 2015, Tanjungsari Village in Pacitan Regency began receiving financial assistance from the government based on Law Number 6 of 2014 concerning Villages. This assistance is provided to support development and empowerment of local communities. These villages are used by the village government and community to evaluate village road facilities and improve village offices so they can provide better services to village residents.